MODULAR BEHAVIOR VILLAGE CONCEPT TO IMPROVE THE QUALITY OF FISHERMEN'S SETTLEMENTS, CASE STUDY : BARRANG LOMPO ISLAND, MAKASSAR - Aldi, Muhammad; Latif, Sahabuddin; Amalia, Andi Annisa; Yusri, Andi; Amal, Citra Amalia; Paddiyatu, Nurhikmah (Universitas Telkom, 2024)
The coastal areas of Makassar City face challenges such as population growth, environmental abrasion, land use conflicts, slums and the emergence of settlements on the water that impact the livelihoods of fishermen and marine resources. This phenomenon emphasizes the need for architectural design that focuses on the order of fishermen's settlements. The research location of the fishermen village arrangement design on Barrang Lompo Island, Sangkarrang Islands District, Makassar City RW004 is mostly inhabited by Jolloro fishermen, an area of 4.14 Ha with a population of 213 people / 216 family heads. The diversity of the island's potential is the basis for considering the need for a structuring concept with a typical fishermen's thematic village theme to maintain the uniqueness and sustainability of Barrang Lompo Island. The results of the concept design of the area arrangement consist of 3 main functions, namely residential, independent economic center, and tourism. In the concept of site arrangement, there are residences, green open spaces, fields, ARSINUM, RESERVOIR, UMKM corner, fishing and tourism docks, and interaction spaces. By applying the Modular Behavior concept, it is expected to provide ease of development and modification in the future, energy efficiency, and the use of environmentally friendly materials. This concept can be a reference for the concept of revitalization of the fishing village area in the case study of RW004 Barrang Lompo Island, Makassar City and can be applied to coastal areas and small islands in Indonesia with different conditions. Keywords : abrasion, area planning, barrang lompo island, modular concept, sustainability